Ocenjevanje in urjenje dinamičnega ravnotežja pri zelo počasni hoji z uporabo rehabilitacijskega robota - Zadravec, Matjaž (Rehabilitacija (Ljubljana), 2022)
Methods and findings of perturbation-based assessment and training of dynamic balancing responses during slow treadmill walking in healthy and impaired subjects are presented. Responses following inward pushes to the pelvis do not differ across walking speeds and consist predominantly from placing an ensuing step into the direction of the perturbing push. Responses to outward pushes differ considerably. At very low walking speed, adequate modulation of centre-of-pressure and ground reaction force under the stance leg are the core of an efficient response. A substantial number of people after stroke or transtibial amputation are not able to respond in the described way and need to negotiate perturbations only when they enter the stance with their unimpaired limb, thus making their responses inefficient. Prolonged perturbation-based training in post-stroke patients may substantially improve recovery of dynamic balancing responses.
Keywords: balance assessment; balance training; dynamic balance responses; Gait; hoja z uporabo motilnih sunkov; možganska kap; ocenjevanje ravnotežja; perturbed walking; ravnotežni odzivi; rehabilitacijska robotika; rehabilitation; rehabilitation robotics; Robotics; stroke; transtibial amputation; transtibialna amputacija; urjenje ravnotežja